A Values-Based Approach for Development: An Islamic Perspective = nhǧ āltnmīa ālqāīʾm ʿlā ālqīm: mnẓūr āʾslāmī - Deif, Ahmed M. (Journal of Islamic ethics, 2022)
Recurrent and concurrent crises call for new development paradigms, as dominant theories of economic development are not fostering equity or sustainability. We argue that part of the reason is that the conceptualization of development, and the resulting metrics driving decision-making, are narrow. Building on work that proposes adding values/ethics as a fourth pillar to development, along with economic, environmental, and social pillars, this article presents an Islamic perspective of how values-based development would differ from the dominant, contemporary forms. While rooted in a specific perspective and worldview, it has great relevance as approximately a quarter of humanity adheres to the faith. We offer a holistic, values-based approach to development, drawing on classical foundations and contemporary lessons, rooted in a different epistemic and ideological orientation. On this basis, we highlight five values that could be the foundation for re-orienting development: vicegerency, justice, excellence, tranquility, and freedom. Integrating these values in a fourth, values-based pillar of development alters the conceptualization and the metrics of development, resulting in processes driven by different objectives for individuals and societies.